INTEGRATION BETWEEN REASON AND REVELATION IN THE GROUNDING OF ISLAMIC LAW IN THE CONTEMPORARY ERA - J, Jumarni; M, Misbahuddin; K, Kurniati (Institut Agama Islam Negeri Bone, 2024)
The purpose of this study is to investigate the formulation of the dilemma concerning the incorporation of revelation and reason in the foundation of Islamic law in the contemporary era. The inquiry that has been posed for investigation is as follows: In what ways might the combination of reason and revelation have an impact on the evolution of Islamic law in the present day? The method that is utilized is library research with a descriptive-analytical approach. In this method, the author examines relevant material in order to get insights into this integration. The findings of this study suggest that the combination of reason and revelation has the potential to not only offer solutions to the problems that are currently confronting Islamic law, but also to encourage the construction of laws that are more sensitive to the advancements that have occurred in the areas of social governance, politics, and the economy. It is anticipated that this research will make a contribution to the creation of Islamic law that is both adaptable and just in the context of the modern world.